ULTRASTRUCTURAL ORGANIZATION OF THE LYMPHATIC CAPILLARIES IN CONJUNCTIVA AND THE LYMPHATIC CHANNELS IN HUMAN CHOROID - S. R. Nogovitsina; N. P. Bgatova; A. V. Eremina; A. N. Trunov; V. V. Chernykh; V. I. Konenkov (Сибирский научный медицинский журнал, 2019)
The aim of this work was a comparative study of the ultrastructural organization of lymphatic structures in the choroid and conjunctiva of the human eye. Material and methods. Samples of the choroid and conjunctiva of the human eye, obtained perioperatively, were studied by immunohistochemical analysis using specific antibodies to endothelial cells markers of blood and lymphatic vessels, and electron microscopic studies, morphometric processing and statistical analysis of the results were performed. Results and discussion. Within simultaneous immunohistochemical staining of conjunctiva and choroid samples using antibodies to markers of lymphatic vessels (LYVE-1, Prox1, podoplanin) the positively stained typical lymphatic vessels have been revealed in the conjunctiva structure and positively stained channels with narrow elongated cells, fibroblasts and pigment cells in choriocapillar layer of the choroid and the transition zone between choroid and sclera. Electron microscopic study revealed that cells expressing lymphatic markers and forming lymphatic channels in the choroid have an ultrastructural organization that is differ from typical lymphatic vascular endothelial cells: they do not have stropic filaments, contain a greater volume density of the granular endoplasmic reticulum membranes, and a lower volume density of mitochondria and micropinocytotic vesicles. The data obtained indicate that the lymphatic pathways of the intraocular fluid outflow in the human eye choroid have organ-specific structural features.